Theoretical and Empirical Analysis of Regional Advantages Theories and Modeling for Advantage Determination of Different Sector in Regions - Hojjatullah Abdolmaleki; Nematullah Akbari; Kiomars Aghaei (فصلنامه پژوهش‌های اقتصادی ایران, 2009)
In empirical microeconomics analysis, the decision making pattern of firms for the site location is very important. Additionally, regarding the lack of information in real economic situation and because of the shortage in resources, analysis of advantageous level of different regions subject to different products is necessary for guiding and encouraging private entrepreneurs and improvement of resource allocation. Thus theoretically and practically two questions may be asked: first, according to the wide range of theories in this area and specialty of each, regarding different aspects of the problem (production costs, accessibility to facilities, …) how is possible to develop a comprehensive theoretical base for practical advantageous analysis? Second, regarding this comprehensive theoretical base, in the case of Iranian provinces how is the advantageous patterns for production development in different regions (provinces)? Seeking for answers to these questions, initially we analyzed advantageous theories and tried to develop the comprehensive theoretical base. As this theoretical base emphasizes on different factors on advantageous determination, we followed up using multi-criteria decision making models, especially Weighted Numerical Taxonomy and Analytical Hierarchy Process for measuring advantageous coefficients of 33 sector in 30 provinces, using 25 important factors. The average of correlation coefficients in these two methods- NT and AHP- was 0.87 suggesting that these methods are highly substitution in advantageous analysis.